bank sampah Pengembangan Bank Sampah Guna Meningkatkan Nilai Ekonomi Masyarakat dan Bentuk Partisipasi Masyarakat Dalam Pengelolaan Sampah - Khairunisa Khairunisa; Mohammad Imam Sufiyanto (Jurnal Nasional Pengabdian Masyarakat, 2023)
This community service is an activity that aims to help the community to be able to reduce the impact of waste and make waste a blessing. Garbage is until recently a serious problem for us. This is a complex environmental problem and tends to increase when the population increases along with the speed of development and economy of a region. To overcome these problems, the community should be aware of the importance of the surrounding environment. One of the community participation is by holding a waste bank program. Waste banks are one of the strategies for implementing 3R (reduce, reuse, recycle) in waste processing at the community level with an economic incentive pattern. Integrated waste processing can stimulate community creativity and innovation so as to improve the welfare of residents. Waste can be a source of economic empowerment of the community, by recycling it into unique items that make money. The focus of this service is to form a community that cares about waste and develop waste banks into one of the activities in the circular economy that can help the economy of people affected by waste which is thrown into the environment every day